Limits of disclosure regulation in the municipal bond market - Ivan T. Ivanov; Tom Zimmermann; Nathan Heinrich (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We examine recent regulation requiring US municipal governments to disclose private debt. We show that governments fail to disclose 55-80% of reportable debt events and that, conditional on disclosure, filings often omit contract details essential for bond pricing. Non-compliant issuers are also riskier than compliers, with disclosure decreasing in the potential of private debt to adversely affect bondholders. Event studies suggest that disclosure reveals positive news and is especially informative to investors in low-rated bonds or during market turmoil episodes. Overall, private debt disclosure remains largely voluntary, highlighting challenges to recent federal initiatives to increase transparency for municipal bond investors.
Keywords: 330; Bond pricing; disclosure regulation; private debt